THE NATIONAL UPGRADING PROGRAM AND SME COMPETITIVENESS IN ALGERIA: INSIGHTS FROM BLIDA PROVINCE (2010–2017) (Lex localis - Journal of Local Self-Government, 2025)
Small and medium enterprises (SMEs) represent the cornerstone of global economic activity due to their vital role in fostering economic growth. They are distinguished from large and multinational corporations by specific characteristics. Like many other countries, Algeria has taken steps to upgrade its SMEs by enacting various laws and regulations to revitalize this sensitive sector, open up to the global economy, and accelerate negotiations to join the World Trade Organization (WTO). This process would result in Algerian markets opening up to highly competitive foreign products, thereby increasing the competitiveness of local products and enhancing non-hydrocarbon exports. Accordingly, this study aims to assess the contribution of the National Upgrading Program (2010–2017) to the development of SMEs in Blida Province, Algeria. A mixed-methods research approach was adopted, utilizing questionnaires and interviews to address the research questions and objectives. This study presents significant findings and implications that may assist policymakers and stakeholders in analysing and revising current policies. It also offers insights into the current state of SMEs in Algeria, their needs, and ways to enhance their capabilities.